Оптимальне коригування ставки податку на галузі для інвесторів у Данії - Пістунов, Ігор Миколайович; Кізілова, Ксенія Сергіївна (My University, 2023)
У статті розглянуто можливість встановлення диференційованих ставок на корпоративний прибуток на прямі іноземні інвестиції у різні галузі Данії з метою підвищення економічного зростання країни за допомогою моделі лінійного програмування, беручи до уваги метод оцінювання експертних висновків, стосовно граничних меж на зміну податку. Висновки експертів перевірено на узгодженість та розраховано ставку корпоративного податку на прибуток за галузями економіки Данії за даними 2022 р.

The paper considers the possibility of setting differentiated corporate profit rates on foreign direct investment in various industries in Denmark in order to increase the country's economic growth. The development of one of the authors regarding the determination of equilibrium prices in retail trade was taken as the main method. According to this method, prices were raised for those goods that sold better. On the contrary, the prices of low-demand goods decreased. A test of that technique in the retail trade proved that customers who bought goods that went up in price did not abandon those goods. On the other hand, the sales of low-demand goods increased, as a result of which the traders' incomes increased. The adaptation of this principle for the reorganization of the taxation system was based on the idea that if the tax on a certain branch of the economy, which gives the largest income to the budget, is increased, investors will not refuse to invest it in the future, and a decrease in the tax on the branch that gives small deductions to the budget of the country, on the contrary , will attract additional investments
Optimal industry tax rate adjustment for investors in Denmark
Keywords: прямі іноземні інвестиції; диференційований корпоративний податок на прибуток; лінійне програмування; метод оцінки експертних висновків; економіка Данії; foreign direct investment; differentiated corporate income tax; linear programming; expert opinion evaluation method; Danish economy